Evaluating Effective Informal Spaces in Schools through Spatial Design Factors and Student Experiences: “Case in Kathmandu Valley” - Upadhyaya, Sarita; Uprety, Sanjaya (Journal of Engineering Issues and Solutions, 2026)
In our educational process, learner-centered cooperation is taking the place of teacher-centered learning. Students spend a significant portion of the day in “informal spaces” (IS) such the corridor, lobby, hall, canteen, patio, and stairway, even though conventional classrooms serve as the primary setting for instruction. Outside of traditional classroom settings, schools’ informal interior spaces are crucial for fostering social interaction, independent study, and overall student wellbeing. In terms of how they enhance the student experience, engagement, and sense of belonging, they are significant but little-researched areas. Despite the fact that these spaces can have significant effects on students’ emotional affinity and connection to their educational environment, they are comparatively understudied in the Nepali school system. This study evaluates the effectiveness of such spaces at two selected secondary schools in the Based on spatial design elements and student experiences, this study employs a mixed-methods approach that includes site inspections, behavioral mapping, focus groups, area measures, and student questionnaires to assess the effectiveness of such spaces at two selected secondary schools in the Kathmandu Valley. About 22–28% of the interior space is dedicated to the main areas for informal activities: the lobby, library nooks, stairs, and hallway. Students think these spaces are good for social interaction, but they also point out that there aren’t enough safety lighting or acoustics. Flexible seating areas, more natural daylighting, and strategic placement near popular areas are recommended design needs to optimize future school designs in Nepal.